2022
DOI: 10.1186/s12992-022-00832-6
|View full text |Cite
|
Sign up to set email alerts
|

Cross-border mobility responses to COVID-19 in Europe: new evidence from facebook data

Abstract: Background Assessing the impact of government responses to Covid-19 is crucial to contain the pandemic and improve preparedness for future crises. We investigate here the impact of non-pharmaceutical interventions (NPIs) and infection threats on the daily evolution of cross-border movements of people during the Covid-19 pandemic. We use a unique database on Facebook users’ mobility, and rely on regression and machine learning models to identify the role of infection threats and containment poli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…A substantial proportion of participants decreased their number of cross-border visits during the pandemic. Prior research in 25 country pairs using phone and Facebook similarly demonstrated a sharp decline in CBM of up to 82% compared to pre-pandemic levels ( 28 ). Compared to Belgium and German participants, Dutch participants more frequently showed an increase in both overall visits and short visits, adjusted for other characteristics.…”
Section: Discussionmentioning
confidence: 91%
“…A substantial proportion of participants decreased their number of cross-border visits during the pandemic. Prior research in 25 country pairs using phone and Facebook similarly demonstrated a sharp decline in CBM of up to 82% compared to pre-pandemic levels ( 28 ). Compared to Belgium and German participants, Dutch participants more frequently showed an increase in both overall visits and short visits, adjusted for other characteristics.…”
Section: Discussionmentioning
confidence: 91%
“…The groups of people at high risk for stigmatization are truck drivers, sex workers, migrants, returnees, and displaced individuals ( 25 , 26 ). Efforts to control the cross-border transmission of COVID-19 can be hampered by political and economic factors that can cause people working in the cross-border area to be unwilling to undergo testing ( 27 ). However, worldwide, the pandemic has impacted the mental health of millions of people by increasing levels of fear, stress, anxiety, and uncertainty.…”
Section: Discussionmentioning
confidence: 99%
“…Docquier et al show how the inclusion of extra parameters (to incorporate day-specific effects-i.e., 366 day-specific time dummies) in their models deteriorates the predictive power of the ML model. The authors conclude that, given a dataset, the gains from adding information are indeed outbalanced by the costs linked to the inflated dimensionality of the AI computation problem [18]. Hinns et al study XAI generated by various predictors on a dataset and show how inconsistent model interpretations emerge among a set of random data sub-sets when using little data, and that by increasing the size of the data, interpretations of the random data subsets converge towards each other [19].…”
Section: Missing Datamentioning
confidence: 99%